Incidencia jurídica de la calificación a organizaciones criminales como terroristas y belingerantes en Ecuador - Paredes Suarez, Alex Wellington (2025)
ABSTRACT This research stems from the classification that was done by the Ecuadorian government to criminal organizations as terrorists and belligerents. This article was developed in the context of the high crime rates in the country, where the executive power has stood out for taking extreme measurements such as declaring states of emergency and categorizing criminal organizations under new categories. The objective proposed for this research is to critically and legally analyze the impact of categorizing criminal organizations as terrorists and belligerents and the impact in the reduction of crime rates in Ecuador. This work was developed through a mixed approach with qualitative predominance, and it was based on the study of jurisprudence, doctrine, current regulations, and the application of a survey. When applying these techniques, the main results showed that this categorization of the criminal organizations done by the government does not have a positive impact in the reduction of the criminal rates. On the other hand, it undermines the rule of law and international relations. As a conclusion, this classification could be aimed to divert attention of the inefficiency instead of providing an effective solution for the reduction of criminal rates in the country. KEYWORDS: criminal organizations, state of emergency, internal armed conflict, terrorists, belligerents.